The relationship between the mental health status and social support of the lonely elderly with government participation in the Internet context - Guo, Jun; Ling, Wenhao (Frontiers in Public Health, 2022)
Objective. At present, urban community aging has become a new way to solve aging problem and has made outstanding contributions to alleviate current aging dilemma. However, there are still deficiencies in the services provided by this new method of community-based elderly care for the elderly who are left alone. Therefore, this paper explores the problems of government policies, facilities and services for the elderly who have lost their independence, analyzes the reasons behind them, and proposes countermeasures. Method. This paper introduces and compares the government's current services for the elderly who are left alone in the city at the level of community-based elderly care services. From the existing literature, we find that most researchers have studied the single-parent family as an individual, exploring its elderly care dilemma, analyzing the causes and proposing countermeasures. It introduces and summarizes the situation of the elderly left alone in Taiyuan, the government's policies on the elderly left alone and community elderly care, the current community elderly care construction in Taiyuan, and the service models provided by the government. Results/Discussion. This paper provides a detailed description and in-depth analysis of the lack of elderly care protection in communities, and analyzes the underlying causes. Activity theory suggests that even though older people are no longer in the same mental state as younger people, they can still enhance their self-worth through active participation in social activities and gain a sense of social identity through social activities. The services provided by social organizations are typical services purchased by the Health and Welfare Commission for the elderly who are left alone, and it is feasible to gradually extend the services to provide more specialized community-based elderly care services for the elderly who are left alone. Therefore, this study takes the use of services provided by social organizations as an example to understand the current situation of services received and used by the elderly who are left alone, and concludes that the services are weakly accessible, and finally proposes suggestions to improve the accessibility of services in three aspects: supply, delivery, and use.